Characteristics of 137Cs accumulation by Quercus serrata seedlings infected with ectomycorrhizal fungi. Issue 1 (2nd January 2018) - Choi, Dongsu; Toda, Hiroto; Guy, Robert D.
ABSTRACT: To study the effects of inoculation with ectomycorrhizal fungi on the accumulation and distribution of radiocesium ( 137 Cs) in different plant organs (leaves, stems and roots), we measured the uptake and internal distribution of 137 Cs by ectomycorrhizal and non-ectomycorrhizal Quercus serrata seedlings in contaminated forest soil. Contamination was a result of the Fukushima Dai-ichi nuclear Power Plant accident. We also estimated the transfer factor (TF), photosynthetic rate and growth of Q. serrata seedlings during the study period, which lasted a full year. The seedlings were grown in plastic pots under field conditions. The soils used in this study had been contaminated with 7200 Bq kg −1 dm of 137 Cs at Fukushima in 2011. The concentration of 137 Cs in the plant organs varied between 148, 252 and 294 Bq kg −1 dm in the non-ectomycorrhizal treatment regime for stems, leaves and roots, respectively, and was 47, 69 and 219 Bq kg −1 dm in the ectomycorrhizal treatment regime. The TF was significantly lower ( P < 0.01) in the ectomycorrhizal treatment regime EC, and apparent quantum yield (α) and maximum photosynthetic rate at light saturation ( P max ) was significantly higher ( P < 0.01), although the growth parameters (stem diameter, height and dry mass) did not differ significantly.